(untitled) (Journal of the College of Education for Women, 2019)
This study seeks to examine the language context of the prominent Revolution’s poet, Moufdi Zakaria, in his anthology “ The Algerian Odyssey " )إلياذة الجزائر( in which he makes use of the Coranic terms explicitly and implicitly. Besides, it seeks to explore the content of his terms from a lexicographic and semantic point of view in their Islamic and human dimensions